Tax Policy and the Dynamic Demand for Domestic and Foreign Capital by Multinational Corporations - Rosanne Altshuler; Jason Cummins (Rutgers University, Department of Economics, 1998)
The extent to which domestic and foreign operations of multinational corporations (MNCs) are related has important implications for the analysis of investment demand and its responsiveness to tax policy. We estimate the structural parameters of a model in which domestic and foreign investment interact in two important ways. First, the MNC's production technology allows the marginal products of domestic and foreign capital to be interdependent. Second, the marginal adjustment costs of investment in one locaton may be affected by investment in other locations. We estimate the model using firm-level panel data from Canadian MNCs that invest solely in the United States. Our estimtes support the view that production and adjustment cost technologies are related. We find that domestic and foreign capital are greater than unit elastic substitutes and that investment in one location lowers the marginal adjustment cost of investment in the other location. We use our parameter estimates to simulate the effect of various tax policies on the growth of parent and affiliate capital stocks. The simulations demonstrate that allowing for interdependent capital demand across locations has important implications for the analysis of tax policy towards MNCs.
Keywords: D24; E22; F21; 330; International factor substitution; International taxation; Investment; Production